O ethos do cooperativismo em diálogos e afetos - Zequetto, Antonio Cleber (2023)
This thesis conducts a study on cooperativism relating it to contemporary research on culture and society. The fundamental theories are cartography and semiotics of culture, the same ones that provide the guidelines for the methodological framework. The thesis focuses on the cause of cooperativism in contemporary scenarios and investigates its constitutive phenomena in the search for understanding and relationships that are established between its precursors and the communities in which they operate, from the perspective of the social relevance generated by this movement. The main objective is to analyze the affections in the dialogues of people involved and engaged in the dynamics and development of cooperativism, as well as in other segments of society in the state of Mato Grosso. The reports and the collective production obtained in the cartographic intervention with academic students of the faculty of cooperativism (Icoop) are analyzed, in the search to understand the ways in which they assimilate the nuances of the cooperative model in their daily lives. The ethos is a concept that refers to the values, beliefs and customs shared by a social group and the study of the semiotics of culture, although to a certain extent, it is focused on signs and symbols and their relationship with language and communication, of interest. if also for the same issues as the ethos, since these form the culture, which favors the dialogue between both. Therefore, they are related when it comes to understanding how the ethos is constructed and communicated through signs and symbols. This research is justified, insofar as the knowledge generated and provided by the universal principles of cooperativism (originated in the principles of Rochdale), are qualified and defended as the ethos of cooperativism under the aegis of being allies in the interpretation and defense of democracy, valuing life, human values and promoting cooperation, as they corroborate for the good performance of social and emotional roles and with the spirituality of subjects in society. In addition to being one of the few works to be dedicated to the subject, from the perspective of culture, so far.